2014
DOI: 10.4103/0970-2113.129871
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of underlying pulmonary sequestration in a patient with recently diagnosed medium and large vessel vasculitis

Abstract: Vasculitis of medium- and large-sized arteries is an inflammatory and stenotic disease characterized by a strong predilection for the aortic arch and its branches. It presents with symptoms and signs as per the vessels and organs involved. Pulmonary sequestration is a rare abnormality characterized by a mass of nonfunctioning lung tissue that receives its vascular supply from a systemic artery and is separated from the normal tracheobronchial tree. The following is a rare case report showing the presence of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Infected pulmonary sequestration due to mycobacteria, such as Mycobacterium tuberculosis and Mycobacterium avium-intracellulare complex, occur rarely[ 1 ]. Malik et al [ 3 ] also demonstrated an asymptomatic intralobar pulmonary sequestration, associated with medium - and large vessel vasculitis[ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infected pulmonary sequestration due to mycobacteria, such as Mycobacterium tuberculosis and Mycobacterium avium-intracellulare complex, occur rarely[ 1 ]. Malik et al [ 3 ] also demonstrated an asymptomatic intralobar pulmonary sequestration, associated with medium - and large vessel vasculitis[ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malik et al also demonstrated an asymptomatic intralobar pulmonary sequestration, associated with medium -and large vessel vasculitis (3). …”
mentioning
confidence: 98%